(untitled) (American Journal of Society and Law, 2024)
This research explores the influence and impact of international organisations on the development and formation of customary international law. It specifically examines the 2018 Draft Conclusions issued by the International Law Commission (ILC). This paper has observed the implications of these findings on the evolution of peremptory norms, also known as jus cogens, and clarifies the scientific approaches used in their identification and legal consequences. Moreover, it emphasises alternative methodologies within the realm of humanitarian action in influencing customary international law. Research offers a thorough comprehension of which international organisations contribute to the development of customary international law. The (ILC)’s 2018 Draft Conclusions shape customary international law by defining peremptory norms (jus cogens). State practice and opinio juris produce conventional rules, as these findings show. They also help evaluate governmental announcements, official publications, legal opinions, and diplomatic exchanges. These results must be assessed for compliance with customary law, state practice, and state behaviour. Alternative analyses like humanitarian intervention and R2P also shape customary international law.